ANALISIS PERENCANAAN PEMBELAJARAN TEMATIK KELAS RENDAH DI MIN 8 TAPIN - Nurul Fauziah (Institut Agama Islam Darul Ulum Kandangan, 2022)
Abstract The thematic learning needed good preparation by teachers, from planning and learning to media preparation by following the purpose of instruction. This study aims to plan to analyze a low in learning and thematic Tapin 8. This study is the type of field research ( field research ) by adopting both qualitative. As for analysis techniques technical data using qualitative descriptive analysis. Based on the research, planning for the teacher thematic learning for the low grade in min Tapin 8 is good, following the year 2019 Permendikbud number 14, which mentions 3 components required in lesson plans. Namely, the purpose of learning, learning steps, and how those lessons. But, several aspects of the components to support each lesson plan have not been full. Key words: Planning Learning, Thematic, Low Grade.